Taxonomic revision of Sobralia section Racemosae Brieger (Sobralieae, Orchidaceae) - Baranow, Przemyslaw; Szlachetko, Dariusz; Kindlmann, Pavel (Frontiers in Ecology and Evolution, 2023)
Sobralia Ruiz & Pav. is a large and morphologically diverse Neotropical orchid genus. It can be divided into few sections and groups of species based mainly on the inflorescence architecture. While most of the species have strongly abbreviated, compact raceme, the section Racemosae is characterized by elongated inflorescence with distinct internodes between flowers. Although the group is well defined and easily distinguishable in terms of morphology, its species are often similar to each other and may be easily misidentified. Identification is especially difficult when considering the herbarium specimens. Here, a taxonomic revision of Sobralia section Racemosae is presented to facilitate the field and herbarium study of the group. Apart of particular species morphological characteristics, key for determination, ecological data and distribution maps are presented. Sobralia gambitana is described as a species new to science. A neotype for S. hoppii Schltr. is suggested.